Rho GTPase ROP1 Interactome Analysis Reveals Novel ROP1-Associated Pathways for Pollen Tube Polar Growth in Arabidopsis - Li, Hui (Int J Mol Sci, 2020)
ROP (Rho-like GTPases from plants) GTPases are polarly localized key regulators of polar growth in pollen tubes and other cells in plants. However, how ROP GTPases are regulated and how they control polar growth remains to be fully understood. To gain new insights into ROP-dependent mechanisms underlying polar cell growth, we characterized the interactome of ROP1 GTPase that controls Arabidopsis pollen tube (PT) tip growth, an extreme form of polar cell growth. We established an efficient method for culturing Arabidopsis pollen tubes in liquid medium, which was used for immunoprecipitation/mass spectrometry-based identification of ROP1-associated proteins. A total of 654 candidates were isolated from the ROP1 interactome in Arabidopsis pollen tubes, and GO (Gene Ontology) classification and pathway analysis revealed multiple uncharacterized ROP1-dependent processes including translation, cell wall modification, post transcriptional modification, and ion homeostasis, in addition to known ROP1-dependent pathways. The ROP1-interactome data was further supported by the co-expression of the candidate interactors in highly mature pollen with PT germination and growth defects being discovered in 25% (8/32) of the candidate mutant genes. Taken together, our work uncovers valuable information for the identification and functional elucidation of ROP-associated proteins in the regulation of polar growth, and provides a reliable reference to identify critical regulators of polar cell growth in the future.